Laundry Section Collaboation With Front Office Department In Conducting Guest Laundry Billing Process at Tentrem Hotel Semarang - Dwi Prinsa Pratiwi; Izza Ulumuddin Ahmad Asshofi (International Forum of Researchers and Lecturers, 2023)
This final project aims to describe the collaboration of laundry section with front office department and describe the constraints that occur between the collaboration of the laundry section and the front office department in conducting guest laundry billing process at the Tentrem Hotel Semarang. The existence of cooperation constraints between the Front Office and Housekeeping raises problems that can cause guest complaints. Therefore, it is necessary to have good quality cooperation between the front office and the laundry department in order to reduce work errors and guest complaints. The research method used is descriptive qualitative method through observation, interviews and retrieval of documentation. The results showed that the collaboration between the laundry section and the front office department went well and smoothly. With the laundry working closely with the front office department to provide information related to guest information that performs laundry services, namely ensuring communication between the front office department and the laundry runs smoothly including information given to guests regarding the clothes they are washing, ensuring there is no damage to guest clothes, always ensuring that laundry delivery to guests is correct and according to guest wishes, the Front Office provides complete information about rooms that benefit from free laundry and laundry Packages. In addition, the Laundry Section cooperation with the Front Office Department in carrying out the Billing process runs according to standard operating procedures. The procedures carried out involve guests, Laundry Attendant, Receptionist and Guest Service Center. In the guest laundry service, then the collaboration also involves Finance to finalize payments.